‘Savages’ and Spiritual Engines: Feeling the Machine in H. G. Wells’s Time Machine and ‘Lord of the Dynamos’ - Tamara Ketabgian (Cahiers Victoriens et Edouardiens)
This essay explores the vestigial influence of natural theology, and its discourse of divine design, on H. G. Wells’s fictions of technology. In Natural Theology (1802), an influential text in this spiritual tradition, William Paley envisions a natural world of analogical clocks, which persuade and appeal to viewers through an immersive encounter with material artistry and skill. Although Paley’s star faded in the later nineteenth century, his discourse persists in alternate, technophilic forms—in what Wells calls the technological ‘patter’ of his own science fiction. Wells ironizes and aestheticizes these mechanical models of belief, both in his eponymous ‘time machine’ (1894–95) and in ‘The Lord of the Dynamos’ (1894), which restages Paley’s analogy with a ‘savage’ worshipping the industrial engine. Seeking, above all, to feel the machine, these two works portray communities of intense spiritual affect, supported through sound, sight, and touch. Yet, while The Time Machine offers us fantastical devices that we must take on faith, ‘The Lord’ reads theistic humanism unsparingly against itself, through acoustic bonds that join people and things within an industrial power station. Exposing the freighted colonial subtext of natural theology, Wells anatomizes the modern worship of machinery, comparing the metropolitan British viewers of engines to naïve primitives in their own right.